The Role of Educational Management in Improving Literacy and Numeracy: A Literature Analysis - Tanjung, Bahdin Nur; Elfrianto , Elfrianto (Lembaga Riset Mutiara Akbar, 2025)
Literacy and numeracy are basic skills that are very important in supporting educational success. Literacy involves the ability to read, write, and understand information, while numeracy includes logical and mathematical abilities used in everyday life. This article aims to analyze the role of educational management in improving literacy and numeracy based on a literature review from national and international journals. This study found that effective management strategies, such as the application of transformational leadership and a data-driven approach, have a significant influence on improving these competencies. By integrating these strategies, educational managers can create programs that are more adaptive, evidence-based, and relevant to students' needs. This article also presents strategic recommendations to improve the quality of literacy and numeracy sustainably.